Cultural differences affecting decision-making style: a comparative study between four countries - Dabić, Marina; Tipurić, Darko; Podrug, Najla (Journal of Business Economics and Management, 2014)
The aim of this paper was to identify the impact of national culture on decision-making styles in selected countries: Croatia, Slovenia, Bosnia and Herzegovina and Hungary. The estimation of Hofstede’s dimensions of national cultures and comparative analyses was carried out by using a narrow-sample strategy. The estimated positions on each dimension confirmed the Hofstede’s original research ranking. The result with significant value was the confirmation of the global trend of decreasing power distance and significant movement towards the individualism. Besides the standardization procedure of comparative cross-cultural analyses, variance analyses were used to identify cultural differences in decision-making styles related to complex decisions. The proposition is that complex decisions are, above and beyond all others, the consequence of social and cultural values installed in every individual. Statistically significant dependency was identified for hyper-vigilant and vigilant decision-making style and national culture’s dimensions. A beneficial goal was to identify the differences and the similarities in value orientation and those in the decision-making style which should not be mistreated as they may influence future business cooperation and political and economic integrations within the CEE context.